IMPLEMENTING THE SDGS: IMPLICATIONS FOR REGULATING MARRIAGE AGE IN INDONESIA - Damayanti, Aulia Dwi; Ramadhani, Dwi Aryanti (LPPM STIH Putri Maharaja, 2025)
The amendment to Marriage Law No. 16 of 2019 sets a minimum age limit to protect children, particularly by reducing maternal and infant mortality rates. In reality, before and after the revision, the existence of marriage dispensations that have been granted continues to impact maternal and child health, as outlined in the Sustainable Development Goals (SDGs) under Goal 3. Therefore, this study aims to analyze the implementation of the marriage age limit and the impact of marriage dispensations on achieving the Sustainable Development Goals (SDGs). The research method used is a legal analysis (normative) approach and a legislative and historical approach based on literature reviews. The research findings reveal that challenges to achieving the SDGs still exist, particularly due to the high number of marriage dispensations granted and the increase in maternal and infant mortality rates. This study shows that there are still differences in the interpretation of urgent reasons because judges consider legal, social, and religious aspects in marriage dispensations, resulting in inconsistencies with the objectives of the law revision. Further study is needed regarding urgent reasons to consistently implement Marriage Law No. 16 of 2019 and Perma No. 5 of 2019. Preventive efforts through education on the negative impacts of early marriage, through inter-institutional collaboration, are also essential to enhance legal understanding and public awareness.